the COMPARISON OF MELINJO CHIPS MARKETING CHANNELS IN THE SPECIAL REGIONS OF YOGYAKARTA (DIY) AND CENTRAL JAVA - Sunendar Sunendar; Djeimy Kusnaman; Syahrul Ganda Sukmaya (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2022)
Emping melinjo is one of the processed products from agricultural products. This food is a kind of chips made from old melinjo fruit seeds. Emping melinjo in Bantul Regency is not only marketed in the Yogyakarta area but also outside the region. In Batang emping melinjo Regency, it is not only marketed locally, but also reaches Surabaya, Jakarta and even abroad. The marketing of emping melinjo is often constrained by unstable demand, which is a lot of demand at a certain time. This unstable consumer demand for melinjo chips can be circumvented by production arrangements. However, not all melinjo chips producers are able to make production arrangements. The research method used is descriptive method, by taking all craftsmen respondents who are in Batang Regency and Bantul Regency, while taking merchant respondents by snowball. The marketing of melinjo chips in two different regions, geographical conditions and regional characteristics make two real differences. The marketing channel for emping melinjo in Bantul Regency, DIY has four channels, while in Batang Regency, Central Java, it only has three channels. The channel with the highest number of craftsmen in Bantul as many as 30 craftsmen chose channel I, while in Batang Regency the craftsmen chose channel III to sell their business melinjo chips. The highest profit received by craftsmen/producers occurs in channel I in Batang Regency